Liste Des Sphaeriidae Du Fleuve Saint-Laurent Region De Gentilly - G. Vaillancourt; A. Aubin (Hello World!, 1972)
As a prelude to an ecologic study of Sphaeriidae, the authors made a qualitative and quantitative inventory of waters of the St. Lawrence River in the Gentilly area. We give here the list of the sixteen species which have been recorded.